The Need to Test Hypotheses About Paranoid Schizophrenia: Reply to Clementz and Sweeney - Glick, M.; Zigler, E. (American Psychologist, 1989)
0 citations (Crossref) [2023-10-31]
Keywords: Depressive Disorder; Diagnosis; Differential; Human; Psychiatric Status Rating Scales; Schizophrenia; Paranoid; article; depression; dept.psy; differential diagnosis; human; paranoid schizophrenia; psychological aspect; rating scale

Preventing maladjustment from infancy through adolescence - rickel,au, allen,l - Glick, M (Contemporary Psychology, 1989)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1989CE35400063
Keywords: dept.psy

Theories of probabilistic reinforcement. - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1989)
In three experiments, pigeons chose between two alternatives that differed in the probability of reinforcement and the delay to reinforcement. A peck at a red key led to a delay of 5 s and then a possible reinforcer. A peck at a green key led to an adjusting delay and then a certain reinforcer. This delay was adjusted over trials so as to estimate an indifference point, or a duration at which the two alternatives were chosen about equally often. In Experiments 1 and 2, the intertrial interval was varied across conditions, and these variations had no systematic effects on choice. In Experiment 3, the stimuli that followed a choice of the red key differed across conditions. In some conditions, a red houselight was presented for 5 s after each choice of the red key. In other conditions, the red houselight was present on reinforced trials but not on nonreinforced trials. Subjects exhibited greater preference for the red key in the latter case. The results were used to evaluate four different theories of probabilistic reinforcement. The results were most consistent with the view that the value or effectiveness of a probabilistic reinforcer is determined by the total time per reinforcer spent in the presence of stimuli associated with the probabilistic alternative. According to this view, probabilistic reinforcers are analogous to reinforcers that are delivered after variable delays. 1989 Society for the Experimental Analysis of Behavior
72 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/098-819-689-500-794 tex.type: [object Object]
Keywords: Animal; Color Perception; Conditioning; Operant; Mental Recall; Probability Learning; Reinforcement Schedule; Support; U.S. Gov't; P.H.S.; adjusting schedule; animal; article; color vision; conditioned reinforcement; dept.psy; instrumental conditioning; intertrial interval; key peck; learning; pigeons; recall; reinforcement; reinforcer delay; reinforcer probability

The need to test hypotheses about paranoid schizophrenia: reply to Clementz and Sweeney. - Glick, Marion; Zigler, Edward (American Psychologist, 1989)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/079-001-880-085-55X tex.type: [object Object]
Keywords: dept.psy

Depression: A failure to suppress the self-conscious ‘Monitoring’ of dismal cognitions - Kunzendorf, Robert G; Mclaughlin, Susan (Imagination, Cognition and Personality, 1989)
11 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/061-928-824-373-602 tex.type: [object Object]
Keywords: dept.psy